Anti‐inflammatory compounds to reduce infarct size in large‐animal models of myocardial infarction: A meta‐analysis. (20th January 2015) - van Hout, G.P.J.; Jansen of Lorkeers, S.J.; Wever, K.E.; Sena, E.S.; van Solinge, W.W.; Doevendans, P.A.; Pasterkamp, G.; Chamuleau, S.A.J.; Hoefer, I.E.
ABSTRACT: Targeting the inflammatory response after myocardial infarction (MI) could potentially prevent infarct expansion, resulting in a preservation of cardiac function. Despite extensive testing in large‐animal models of MI, anti‐inflammatory therapeutics are not incorporated in daily clinical practice. Methodological review of the literature describing the effects of anti‐inflammatory compounds in large‐animal models of MI may provide useful insights into the reasons for the translational failure from preclinical to clinical studies. Moreover, systematic review of these preclinical studies may allow us to determine which anti‐inflammatory agents have the greatest potential to successfully treat MI in the clinic and guide which preclinical setting appears most appropriate to test these future treatment strategies in. The current systematic review protocol provides a detailed description of the design of this systematic review of studies investigating the effects of anti‐inflammatory compounds in large‐animal models of MI.